Our Second Son is Number One: Numbers in Recent Japanese Given Names: Nasz Drugi Syn jest Numerem Jeden: Liczby we Współczesnych Imionach Japońskich - Barešová, Barešová (Investigationes Linguisticae, 2020)
Japanese given names reflect through their kanji selection particular perceived or anticipated aspects concerning their bearers, providing an insight into the changing values of Japanese society. In the past, numbers were used in names mainly to refer to the order of birth, the time of birth, or, in the case of large numbers, to express a wish for longevity. Within the larger historical context, this paper focuses on the use of kanji representing numbers in the names of children born in the last ten years (2008–2017), exploring the recent reasons for their choice and what values and priorities of recent Japanese parents they reflect.